Rapid generation of hierarchical nanoarchitectures of CdS via facile microwave assisted hydrothermal/semi-solvothermal route. (18th August 2010) - Shinde, Manish D.; Pawar, Amol U.; Sreeja, V.; Rane, Sunit; Potdar, Hari; Amalnerkar, Dinesh
1-D nanorod bundles as well as sea urchin and starfish like hierarchical morphological nanoarchitectures of CdS have been synthesised using a facile microwave assisted hydrothermal/semi-solvothermal technique. Observation of interesting regular/irregular pine-tree like secondary growth over these hierarchical nanoarchitectures is an important aspect of this work. Cadmium acetate and thiourea were used as precursor materials and were dissolved in solution containing mixture of diethylene triamine (DETA) and deionised water (DIW) in different volume ratios prior to subjecting the resultant solution to microwave radiation of 300 W at a reaction time of 10 min and temperature of 140°C. XRD revealed formation of hexagonal CdS with strong (002) preferred orientation (c-axis orientation). Morphology dependent optical properties are studied using room temperature photoluminescence spectroscopy. We feel such secondary growth will be highly favourable in determining the non-linear properties of optoelectronic devices fabricated using such novel hierarchical nanoarchitectures.